Effect of silicides on tensile properties and fracture of alloy Ti-6AI-5Zr-0.5Mo-0.25Si from 300 to 823 K - Ramachandra C.; Singh V. (My University, 2025)
The tensile properties and fracture behaviour of alloy Ti-6AI-5Zr-0.5Mo-0.25Si (wt%) have been investigated over a wide range of temperature from 300 to 823 K, in the as-water-quenched (WQ) and different aged (473 to 1073 K for 24 h)conditions following β-solution-treatment (1323 K for 0.5 h). There is only a limited increase in strength but a drastic reduction in the ductility, at 300 K, due to ageing at ≥ 923 K. There is strong dynamic strain-ageing (DSA) in the unaged (WQ) state from 623 to 823 K and it is essentially due to silicon in the solid solution. The degree of DSA decreases with the ageing temperature and DSA does not occur in specimens aged at 973 and 1073 K. In general, the ductility of the WQ as well as the aged material increases with test temperature, except in the range of DSA, where the ductility of WQ material is reduced. The mode of fracture of the WQ specimens remains ductile in the lower and higher ranges of test temperature, but changes to quasi-cleavage at intermediate test temperatures. The minimum in the ductility and quasi-cleavage mode of fracture at 773 K, in the WQ material, is due to strong DSA. Three different modes of fracture, namely faceted, ductile, and mixed intergranular and ductile in the lower, intermediate and higher range of test temperature, respectively, are observed also in the aged conditions (at and above 923 K) of the material. The tensile properties and fracture characteristics in the aged conditions are controlled by the silicides. © 1988 Chapman and Hall Ltd.